Utilizing Satellite Imagery for Seasonal Trophic Analysis in the Freshwater Reservoir - Rifa Rachmadita; Ana Widiana; Ade Rahmat; Sunardi Sunardi; Moh Dede (Pandawa Institute, 2024)
Eutrophication, an aquatic problem that impacts water quality and ecosystems, can be addressed through technological developments utilizing satellite imagery to analyze the trophic status of water. This study aimed to determine the trophic status of the freshwater reservoir in different seasons using satellite imagery. Water quality data were obtained from field surveys (11 samples) during the wet and dry seasons in Cirata Reservoir (Indonesia) while the remote sensing images were obtained from the Landsat-8 OLI. Trophic status refers to Carlson's Trophic State Index consisting of two parameters named chlorophyll-A and water transparency. This study found that satellite imagery could estimate seasonal trophic information. During the wet season, the algorithms determined information about chlorophyll-A (48%) and transparency (35%). Whereas during the dry season, the algorithms successfully estimated both information at 59% and 21%, respectively. Unfortunately, the Landsat-8 OLI had limitations for estimating total phosphorus. From these two parameters, the trophic status in the Cirata Reservoir showed moderate (wet season) and mild (dry season) eutrophic. Cirata Reservoir has a higher trophic level during the wet season since it has more surface water supply with lots of pollutants.